Design and Implementation Proximity Based IoT for Smart Attendance System - Hayati, Nur; Eka Nugraha, Aditiyo (Buletin Pos dan Telekomunikasi, 2023)
The reporting of course attendance is an essential component of academic administration. This research designs and deploys a smart attendance system by leveraging proximity-based IoT. The smart attendance system is built upon the Android operating system to detect the beacon of the proximity sensor and is integrated into a database installed on a cloud server. The application supports three different features designated for administrators, lecturers, and students, respectively. The developed application accelerates data input for the campus administrator, records the course log efficiently, and concurrently reports the more secure student attendance from manipulation since it applies a single user identity. This study conducts a field test to evaluate the operational efficacy of the system by sampling students who enrolled in the course. The test involves utilizing a range of mobile devices to access the application connected to two courses. In one course, the functionality testing result is 91.67%, while in another, it is 100% successful. The limitation arises as a result of the incapability of the mobile device to perceive the beacon.